Proměna vnímání upíra v západní kultuře od raného novověku po současnost : posouzení marginálního kulturního jevu v intencích civilizační teorie Norberta Eliase - Konečná, Zuzana (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2013)
The thesis deals with the transformation of perception of vampire in Western culture from early modern period to present. The vampire in modern Western culture is very popular and has an unwavering place. Vampires are now attractive and basically not dangerous. The subject of this work is question whether it was so in previous centuries. Work present the change in appearance and character, both fictional character and "real vampires." Based on the analysis of selected fictional works (literary and visual) from the late 18th century, when the vampire came to Western fiction, work shows how gradually transforms the image that this supernatural beings attributes in West. An essential part of how culture perceives certain phenomenon is a belief in it. Therefore I am interested in how the West over time explaining this phenomenon. Work also introduces the Norbert Elias's civilization theory. Analysis of transformation in the perception of a vampire in Western culture follows it's tracks and the results are compared with it with the goal to give answer on question whether this phenomenon is turning into the terms of this theory.
Keywords: Upír; early modern period; západní kultura; Western culture; současnost; Vampire; civilizační proces; Elias; proměna; raný novověk; Transformation; present; civilization theory